(3CMGOjK ef KdGKjGJ CMeO Hf MfHds - (3CHh MGeO eMeO Hf YHO GdQMef GdeWQis; (3CMeO Hf eMeO Hf MfHd, CHh YHO Gddg, GdTjHGfqj GdhGFdj,J (B241 (3g` s ((3eMeO Hf eMeO Hf CHj TQja GdTGaYi GdebOSi s)
(3ChdgG (B:s
(3CMGOjK ef KdGKjGJ eSfO GdGeGe CHj YHO Gddg CMeO Hf MfHd QVi Gddg Yfg bQCgG HGdJGe daXg HGdeOjfI GdfHhjI HeSLO QShd Gddg Udi Gddg Ydjg hSde TjNfG CHj MGeO eMeO YHO GdQMef GdeWQi s
(3BNQgG (B:s
(3hcGf Pdc HGdQhVI GdTQjaI ef eSLO QShd Gddg Udi Gddg Ydjg hSde hUM Pdc hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YdjgG SeGY ddcGJH hLeGYI Ydi GdTjN GdeWQi hNWg HUMI gPG GdSeGY hcPdc NW CMeO Hf GHQGgje Hf CMeO GdMfHdi HUMI SeGYgG Ydjg ddcGJH hLeGYI GNQjfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs